Analysis of Problems in The Framework of Development of Medical Record Control Systems - Yunita Fitri Widiyawati; Hosizah Markam; Rina Mutiara (Syntax Corporation Indonesia, 2023)
The number of delays in the cause of inpatient medical records in Indonesia is still high, in the range of 45.45% - 100%. Where the highest delay in return is caused by incompleteness in filling out the medical resume, this can potentially cause losses to the hospital due to delayed claim collection. This study aims to analyze the causes of the problem to develop an inpatient medical record control system model using the waterfall model method, including Requirements, Analysis, and Design at Aqidah Hospital, Tangerang City. This case study uses a qualitative approach with in-depth interviews, FGD (Focus Group Discussion), Observation and Document Review of inpatient medical records for October – December 2021. The results showed that the delay in returning inpatient medical records in 2019 was 185 out of 280 (66.10%). In 2020 as many as 280 out of 410 (68.29%), and in 2021 as many as 228 out of 320 (71.25%). ) thus, the highest percentage of delays in returning inpatient medical records will occur in 2021. While the writing of the primary diagnosis only reached the percentage of 1.25%, and the secondary diagnosis only reached 0.93%. For this reason, the researcher proposes a solution to the problem of delaying the return of medical records at Aqidah Hospital to develop a medical record control system model to improve the medical record management process.